2020
DOI: 10.1002/jsfa.10530
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of value‐added glycopeptides from edible bird's nest (EBN) co‐products: enzymatic hydrolysis, physicochemical characteristics and bioactivity

Abstract: BACKGROUND Processing of edible bird's nest (EBN) requires extensive washing to remove impurities and produces huge amounts of EBN co‐products, which contain mainly feathers with glycoproteins attached, which are usually discarded. This study was conducted to recover the valuable EBN glycoproteins from the waste material. Enzymatic hydrolysis was applied to recover EBN glycopeptides from EBN co‐products (EBNcoP) and processed cleaned EBN (EBNclean) was used as control, which were then freeze‐dried into EBN hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 34 publications
(57 reference statements)
0
8
1
Order By: Relevance
“…After the extraction process, the suspensions are centrifuged at 18,000 rpm for 20 min, and the supernatants are thoroughly dialysed against distilled water (Hun et al, 2016). For enzymatic treatment, enzymes such as pancreatin, alcalase (Khushairay et al, 2014), protease from Bacillus licheniformis (Ling et al, 2020), and neuraminidase from C. perfringens (Guo et al, 2006) is used. In continuation of the heating, the enzyme is usually added to the EBN mixture at a warm temperature between 38°C-60°C, at pH 8.5-9.0 to facilitate partial protein denaturation.…”
Section: Laboratory and Traditional Industrial Edible Bird's Nest Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…After the extraction process, the suspensions are centrifuged at 18,000 rpm for 20 min, and the supernatants are thoroughly dialysed against distilled water (Hun et al, 2016). For enzymatic treatment, enzymes such as pancreatin, alcalase (Khushairay et al, 2014), protease from Bacillus licheniformis (Ling et al, 2020), and neuraminidase from C. perfringens (Guo et al, 2006) is used. In continuation of the heating, the enzyme is usually added to the EBN mixture at a warm temperature between 38°C-60°C, at pH 8.5-9.0 to facilitate partial protein denaturation.…”
Section: Laboratory and Traditional Industrial Edible Bird's Nest Processingmentioning
confidence: 99%
“…Proteins: 61.5 ± 0.6 g/ 100 g, Calcium: 553.1 ± 19.5 mg/100 g, Sodium: 187.9 ± 10.4 mg/100 g, Magnesium: 92.9 ± 2.0 mg/100 g, Potassium: 6.3 ± 0.4 mg/100 g Sialic acids: 0.7-1.5% -- USD kg −1 and unprocessed EBN was 1200-1500 USD kg −1 in 2017, and this value is expected to increase in the future. The salvation step should be included in enzymatic extraction procedure to prevent economical and nutritional value loss (Ling et al, 2020 Several studies demonstrated plausible authentication methods could be translated into industrial settings, but cost-effectiveness and equipment availability required further analysis and comparison. Numerous in vivo animal studies showed promising health-improving functions of EBN with discoveries of bioactive compounds.…”
Section: Hydrochloric Acid Extractionmentioning
confidence: 99%
“…The powder samples were kept in airtight container. Ling et al (2020) Commercial EBN products from Mobile Harvester (M) Sdn Bhd, Selangor, Malaysia…”
Section: Storagementioning
confidence: 99%
“…Most of the studies investigating the potential medicinal values of EBN used water extract (Haghani et al, 2016;Haghani et al, 2017), as bioactive compounds in EBN are water-soluble. Water extraction of EBN results in a mixture of glycopeptides (Guo et al, 2006;Yagi et al, 2008;Ling et al, 2020;Hui Yan et al, 2021) which should be isolated or purified through a binding affinity technique utilizing specifically targeted ligands anchored to the FIGURE 2 | In severely ill influenza patients, immune cells release various cytokines and chemokines leading to acute lung injury, or also known as acute respiratory distress syndrome (ARDS) due to apoptosis. In severely ill COVID-19 patients, various immune cells release a myriad of chemokines and cytokines causing apoptosis, leading to ARDS and spillover of cytokines and chemokines into the blood circulation causing multi-organ failure.…”
Section: Bioactive Ingredients In Ebnmentioning
confidence: 99%
“…EBN produces a great deal of EBN by-products during the processing, which is difficult to be effectively utilized or discarded, resulting in a certain amount of waste [ 22 ]. Studies have shown that there is no significant difference in the nutritional composition of EBN by-products and EBN.…”
Section: Introductionmentioning
confidence: 99%